Internet misuse at work in Jordan: Challenges and implications - Alshuaibi, Ahmad Said; Mohd Shamsudin, Faridahwati; Alshuaibi, Mohammad Said Ibrahim (2015)
The Internet has undoubtedly transformed our lives—both at the personal and professional levels. What happens when the Internet is used simultaneously for personal purposes but during work or professional time? This paper seeks to argue that such interaction is one of the challenges that organizations are facing today. We intend to discuss the phenomenon of Internet misuse at work with specific reference to Jordan. As one of the only two countries in the Middle East that has fully liberalized the telecommunications sector, the growing Internet penetration in the country is not without risks. Internet misuse is one likely consequence of the liberalization policy.In this paper, we seek to explain what Internet misuse is, how it is problematic to organizations and how it can be addressed. Though the problem of Internet misuse is not unique to Jordan, we argue that effective measures to tackle the issue are likely to be appropriate to some extent for other countries facing a similar problem.